Recent Progress in Transition Metal-Catalyzed Addition Reactions of H–P(O) Compounds with Unsaturated Carbon Linkages - Tanaka, Masato (Hydrofunctionalization, 2011)
Organophosphorus compounds are playing important roles in our daily life covering a wide range of applications from medicinal use to flame-retardant materials. Although classical synthetic methodologies are still used to synthesize them, the addition reactions of H–P(O) compounds such as H-phosphonates, H-phosphinates, and sec-phosphine oxides have been developed to partially replace the classical methods and are envisioned to be an indispensable tool in the near future. This chapter intends basically to provide recent progress in the field, but not a full scope on the reaction since the same subject was already written by the author in 2004.